FLUID-BEARING ALKALINE CARBONATE MELTS AS THE MEDIUM FOR THE FORMATION OF DIAMONDS IN THE EARTH'S MANTLE: AN EXPERIMENTAL STUDY - Pal'yanov Yu.; Sokol A.G.; Borzdov Yu.; Khokhryakov A.F. (My University, 2002)
We have experimentally studied the formation of diamonds in alkaline carbonate-carbon and carbonate-fluid-carbon systems at 5.7-7.0 GPa and 1150-1700 °C, using a split-sphere multi-anvil apparatus (BARS). The starting carbonate and fluid-generating materials were placed into Pt and Au ampoules. The main specific feature of the studied systems is a long period of induction, which precedes the nucleation and growth of diamonds. The period of induction considerably increases with decreasing P and T, but decreases when adding a C-O-H fluid to the system. In the range of P and T corresponding to the formation of diamonds in nature, this period lasts for tens of hours. The reactivity of the studied systems with respect to the diamond nucleation and growth decreases in this sequence: Na2CO3-H2C2O4.2H2O-C>K2CO3-H2C2O4.2H2O-C>>Na2CO3-C>K2CO3-C. The diamond morphology is independent of P and T, and is mainly governed by the composition of the crystallization medium. The stable growth form is a cubo-octahedron in the Na2CO3 melt, and an octahedron in the K2CO3 melt. Regardless of the composition of the carbonate melt, only octahedral diamond crystals formed in the presence of the C-O-H fluid. The growth rates of diamond varied in the range from 1.7 μm/h at 1420 °C to 0.1-0.01 μm/h at 1150 °C, and were used to estimate, for the first time, the possible duration of the crystallization of natural diamonds. From the analysis of the experimental results and the petrological evidence for the formation of diamonds in nature, we suggest that fluid-bearing alkaline carbonate melts are, most likely, the medium for the nucleation and growth of diamonds in the Earth's upper mantle.
Keywords: DIAMOND; CRYSTALLIZATION; CARBONATE; MELTING; HIGH-PRESSURE EXPERIMENTS